ANALISIS PERAN PEMUNGUTAN PAJAK PARKIR DALAM PENINGKATAN PENDAPATAN ASLI DAERAH DI KOTA BITUNG - Gintoe, Selin; Elim, Inggriani; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The source of the Regional Original Revenue is local tax, one of which is parking tax. In this study, it was described how the practice of parking tax collection, parking tax collection function, contribution and participation in increasing the original regional income of Bitung City, while the research method used was using a qualitative descriptive approach. One source of funds that comes from regional capacity itself is Regional Original Revenue. From the results of this study indicate that the contribution of Parking Tax to support the Original Revenue of Bitung City in 2015-2017 tends to decrease. In 2015 where parking tax had the highest contribution of 152.89% and the low contribution can be seen in 2017 which was 89.17%. The decrease in the contribution of parking tax was due to several causes, namely in fulfilling the taxation regulations that apply to taxpayers lacking a good understanding so that taxpayers have the awareness to pay their due taxes, found several new parking spaces and it is known that they have not been registered as regional taxpayers In addition, there is income from a parking lot whose income cannot be estimated so that the parking lot does not pay the due tax.Keywords : Collection, Parking Tax and Local Revenue